(untitled) (Productivity, 2021)
This study aims to determine whether service quality has an effect on customer satisfaction at PT. Matahari Department Store Mega Mall Manado. This research is a type of quantitative research with a consumer population of PT. Matahari Department Store Mega Mall Manado. The sample size uses the guidelines proposed by Roscoe, that a viable sample size in the study of between 30 and 500 is sufficient to be used in a study. Therefore, the sample in this study was 50 respondents. Judging from the results of the calculation of the hypothesis partially through the t test which states that the variable service quality is known to have a tcount of 11,382 and a ttable of 2,010, it can be concluded that service quality has a significant effect on customer satisfaction. So Ho’s decision is rejected and Ha is accepted, which means that service quality affects customer satisfaction. And based on the results of simple linear regression testing, the influence between service quality variables and customer satisfaction is indicated by the coefficient of determination (R2) of 0.730 or 73.0%, which means that the influence of service quality variables on customer satisfaction is 73.0% while the remaining 27.0% is influenced by other variables that are not included in this study.